2021
DOI: 10.1038/s41598-020-79478-6
|View full text |Cite
|
Sign up to set email alerts
|

The fecal mycobiome in patients with Irritable Bowel Syndrome

Abstract: Alterations of the gut microbiota have been reported in various gastrointestinal disorders, but knowledge of the mycobiome is limited. We investigated the gut mycobiome of 80 patients with Irritable Bowel Syndrome (IBS) in comparison with 64 control subjects. The fungal-specific internal transcribed spacer 1 (ITS-1) amplicon was sequenced, and mycobiome zero-radius operational taxonomic units (zOTUs) were defined representing known and unknown species and strains. The fungal community was sparse and individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
1
31
1
Order By: Relevance
“…By using the culturomics approach, we confirmed an imbalanced fungal community in accordance with results from Gu et al (2019) and Das et al (2021). In both our cohorts, the most abundant fungal species was C. albicans, isolated at higher frequency in IBS patients than HS.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…By using the culturomics approach, we confirmed an imbalanced fungal community in accordance with results from Gu et al (2019) and Das et al (2021). In both our cohorts, the most abundant fungal species was C. albicans, isolated at higher frequency in IBS patients than HS.…”
Section: Discussionsupporting
confidence: 86%
“…In humans, Das et al (2021) showed that the mycobiome composition differentiates patients with IBS from controls, with a significant co-variation between mycobiota and bacteriome. Sokol et al (2017) showed increased intermicrobial kingdom relationship in ulcerative colitis, and reduced interactions between gut bacteria and fungi in Crohn's disease, while results from Imai et al (2019) showed the contrary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysbiosis of the fungal microbiome and involvement of fungi in the pathogenesis of disease has been demonstrated for IBD, colorectal cancer, obesity, and atherosclerosis [236,[244][245][246][247][248][249][250][251], while patients with diabetes mellitus type 1 demonstrated increased fungal diversity [252]. For IBS, fungal dysbiosis was linked to increased intestinal hypersensitivity while the added value of the investigation of the mycobiome for diagnostic or therapeutic aims was doubted in one study [253,254]. Concerning liver diseases, changes of the mycobiome characterized by lower diversity and Candida overgrowth for ALD and by lower diversity and distinct fungal composition in NAFLD were demonstrated [235].…”
Section: Gut Mycobiome 61 Introductionmentioning
confidence: 99%